2013
DOI: 10.1097/hrp.0b013e31828a3612
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms After CABG Surgery

Abstract: Objective Depression is highly comorbid with coronary artery disease. Clinicians face the question of whether patients’ depressive symptoms will improve after coronary artery bypass graft surgery (CABG). The objective of this meta-analysis is to determine the course of depressive symptoms after CABG. Methods EMBASE, PubMed, and PsycINFO were searched for studies assessing depression before and after CABG. Meta-analyses were performed for depression at early (1–2 weeks), recovery (>2 weeks to 2 months), mid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 49 publications
(31 reference statements)
4
42
0
1
Order By: Relevance
“…However, the lack of control data limits our ability to draw any firm conclusions about the comparability of these rates to those of healthy older adults. The rates of clinically significant levels of depression in TJR patients are comparable to those seen in cardiac surgery patients (Ravven, Bader, Azar, & Rudolph, 2013), but are lower than those of thoracic surgery (Kitagawa et al, 2011;Okamoto, Motomura, Murashima, & Takamoto, 2013) and hip fracture patients (Guerini et al, 2010;Phillips, Upton, Duggal, Carroll, & Lord, 2013). The six studies that examined the prevalence of clinically significant levels of anxiety symptoms reported rates that ranged between 9% and 95%.…”
Section: Discussionmentioning
confidence: 92%
“…However, the lack of control data limits our ability to draw any firm conclusions about the comparability of these rates to those of healthy older adults. The rates of clinically significant levels of depression in TJR patients are comparable to those seen in cardiac surgery patients (Ravven, Bader, Azar, & Rudolph, 2013), but are lower than those of thoracic surgery (Kitagawa et al, 2011;Okamoto, Motomura, Murashima, & Takamoto, 2013) and hip fracture patients (Guerini et al, 2010;Phillips, Upton, Duggal, Carroll, & Lord, 2013). The six studies that examined the prevalence of clinically significant levels of anxiety symptoms reported rates that ranged between 9% and 95%.…”
Section: Discussionmentioning
confidence: 92%
“…Cardiac surgeries offer an ideal model to study the association between psychological distress and PPSP. In addition, up to 1/3 of patients undergoing cardiac surgeries experience elevated levels of preand post-surgical depressive and anxiety symptoms (Murphy et al, 2008a;McKenzie et al, 2010;Ravven et al, 2013) and this is associated with worse pain scores in the year following CABG (Karlsson et al, 1999;Choiniere et al, 2014). In addition, up to 1/3 of patients undergoing cardiac surgeries experience elevated levels of preand post-surgical depressive and anxiety symptoms (Murphy et al, 2008a;McKenzie et al, 2010;Ravven et al, 2013) and this is associated with worse pain scores in the year following CABG (Karlsson et al, 1999;Choiniere et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review found that as patients entered the recovery period (2 weeks postoperatively), depressive symptoms measured on standard instruments and depression diagnosis was lower than preoperative levels. 78 Importantly, those who were diagnosed with depression more than 1 week prior to cardiac surgery were less likely to experience depression remission postoperatively. 78 This response to the mental health stress of cardiac surgery can provide valuable insight into cardiac surgery outcomes.…”
Section: Psychological Frailtymentioning
confidence: 99%
“…78 Importantly, those who were diagnosed with depression more than 1 week prior to cardiac surgery were less likely to experience depression remission postoperatively. 78 This response to the mental health stress of cardiac surgery can provide valuable insight into cardiac surgery outcomes.…”
Section: Psychological Frailtymentioning
confidence: 99%